Encapsulation of oxime K027 into cucurbit[7]uril: In vivo evaluation of safety, absorption, brain distribution and reactivation effectiveness. (1st March 2020) - Zdarova Karasova, Jana; Hepnarova, Vendula; Andrys, Rudolf; Lisa, Miroslav; Jost, Petr; Muckova, Lubica; Pejchal, Jaroslav; Herman, David; Jun, Daniel; Kassa, Jiri; Kuca, Kamil
Highlights: Poor BBB passage and fast elimination limit use of oximes in OPs treatment. Cucurbit[7]uril (CB7)was tested as a delivery vehicle for bisquaternary oximes. The encapsulation process, cell toxicity, in vivo safety and influence of CB7 on oxime pharmacokinetics and pharmacodynamics were studied. The encapsulation of K027 increased and accelerated the blood-brain-barrier penetration. The CB7 protects the circulating oxime from rapid renal clearance. Abstract: Oxime-based acetylcholinesterase reactivators (briefly oximes) regenerate organophosphate-inactivated acetylcholinesterase and restore its function. Poor blood-brain-barrier passage and fast elimination from blood limit their actual use in treatment of patients exposed to organophosphates. Previous in vitro results implicated further testing of cucurbit[7]uril as a delivery vehicle for bisquaternary oximes. The present paper focuses on cell toxicity, in vivo safety and influence of cucurbit[7]uril on oxime pharmacokinetics and pharmacodynamics. Neither the K027 nor the complex caused any cell toxicity, changes in blood biochemistry or hepato- or nephrotoxicity in tested concentrations. The encapsulation of K027 increased and accelerated the blood-brain-barrier penetration. The peripheral oxime exposure also increased, supporting the suggestion that cucurbit[7]uril protects the circulating oxime from rapid renal clearance. Contrary to the comparable in vitro reactivation power of K027 and the encapsulated K027, we failed to confirm this in vivo . In theory, this might result from the non-specific binding of molecules to the cucurbit[7]uril or the interaction of K027 with cucurbit[7]uril being too strong for acetylcholinesterase reactivation. Precise explanation requires additional in silico, in vitro and also in vivo experiments.